Key Factors for Successful Development of Offshore Wind in Emerging Markets - World Bank Group (World Bank, Washington, DC, 2021)
Offshore wind holds tremendous promise for many emerging markets as a large-scale, clean, reliable form of new electricity generation with the potential to stimulate valuable economic benefits. However, developing a new offshore wind sector in an emerging market is no easy task. Decision makers must strike a careful balance as they consider a range of technical, political, environmental and social challenges. Offshore wind projectscombine the scale of large hydro and the complexity of offshore hydrocarbon extraction, making them entirely different from onshore wind or solar. Government support and proactivity is, therefore, essential to develop a successful new sector and deliver the high rewards that offshore wind can bring.